2015
DOI: 10.1002/spe.2320
|View full text |Cite
|
Sign up to set email alerts
|

Migrating legacy software to the cloud: approach and verification by means of two medical software use cases

Abstract: SUMMARYCloud computing is a technology that enables elastic, on-demand resource provisioning, allowing application developers to build highly scalable systems. Multi-tenancy, the hosting of multiple customers by a single application instance, leads to improved efficiency, improved scalability, and less costs. While these technologies make it possible to create many new applications, legacy applications can also benefit from the added flexibility and cost savings of cloud computing and multi-tenancy. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Maenhaut et al demonstrated the benefits of migrating the legacy software to the cloud. The authors investigated and confirmed the long term benefits of migrating applications (such as nurse call systems, schedule planner, etc) for managing medical appointments that are widely used within hospitals.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Maenhaut et al demonstrated the benefits of migrating the legacy software to the cloud. The authors investigated and confirmed the long term benefits of migrating applications (such as nurse call systems, schedule planner, etc) for managing medical appointments that are widely used within hospitals.…”
Section: Related Workmentioning
confidence: 99%
“…The conclusion made by the authors is similar to our research work in which we proved effectiveness of test data generation framework over cloud. Although our proposed strategy works with different set of applications, our vision for the significance of working on cloud environment is same as that of the work of Maenhaut et al…”
Section: Related Workmentioning
confidence: 99%
“…Java is a widely used object‐oriented programming language with the characteristics open‐source and cross‐platform . A typical software framework contains presentation layer, business logic layer, and data access layer . This study focuses on the data access and business logic layers.…”
Section: Related Frameworkmentioning
confidence: 99%
“…Similar, Miranda et al (2013) conduct a cloud-to-cloud migration between two IaaS offerings that uses software metrics to calculate the estimated migration costs in man hours rather than making migration efforts explicit. When unveiling occurred effort, the focus is often on operational cost comparisons (Khajeh-Hosseini, Greenwood, & Sommerville, 2010;Khajeh-Hosseini, Sommerville, Bogaerts, & Teregowda, 2011;Tak, Urgaonkar, & Sivasubramaniam, 2011;Andrikopoulos, Song, & Leymann, 2013), e.g., infrastructure costs, support, and maintenance or migration effort in man hours Maenhaut, Moens, Ongenae, & De Turck, 2015). Solely, Ward et al (2010) mention migration metrics related to the effort to create build automation or the server provisioning time comparable to our deployment metrics.…”
Section: Related Workmentioning
confidence: 99%